Smartphone dependency and its impact on purchase behavior - Harun, Amran; Liew, Toh Soon; Mohd Kassim, Abdul Wahid; Sulong, Rini Suryati (Canadian Center of Science and Education, 2015)
People nowadays seem to become dependent towards smartphone due to its convenience, great camera features, easy applications’ installations, and more importantly, it can do most of the computer functions on the go. Significantly, smartphone usage in Malaysia is growing enormously and has become a significant and lucrative industry. This study aims to understand the antecedents and the outcome of the smartphone dependency among smartphone consumers. Two theories - the theory of uses and gratification and the media dependency theorywere used as the theoretical basis for this study, in order to determine the motivations to use a smartphone and to define dependency and its outcome. The antecedent variables were convenience, social need and social influence; and all of these dimensions are conceptualized as one-dimensional. The outcome of dependency on smartphones was expected to be the purchase behavior. Data analyses were based on 226 valid questionnaires that were collected among smartphone users. The result from the Confirmatory Factor Analysis of Partial Least Square (PLS) shows that only social needs and social influence significantly influenced the smartphone dependency among consumers, therefore indicating that these two factors are important to influence dependency on the smartphone. In addition, the analysis also verifies that the purchase behavior is the outcome of the dependency on the smartphone. Based on these results, marketers could focus on creating dependency among consumers on smartphone usage based on the consumers’ social need, which eventually will promote future purchase behavior in the long run. More importantly, understanding social influences as antecedents.